An ultrastable Zr-MOF for fast capture and highly luminescence detection of Cr2O72− simultaneously in an aqueous phase. Issue 15 (22nd March 2018) - Sun, Xiaodong; Yao, Shuo; Yu, Chengyang; Li, Guanghua; Liu, Chunming; Huo, Qisheng; Liu, Yunling
Abstract : A porous Zr-MOFs (JLU-MOF50 ) with exceptional stabilities has been synthesized. As a dual functional material, JLU-MOF50 displays not only a high trapping capacity and an adsorption rate, but also effective detecting performance for Cr2 O7 2− in the aqueous phase. Abstract : Herein, using the modulator synthesis approach, a zirconium-based metal–organic framework (Zr-MOF), [Zr6 O4 (OH)4 L4 (H2 O)2 (HCOO)4 ]·9DMF·12H2 O (JLU-MOF50, L = H2 MDCPB = 5′-methyl-[1, 1′, 3′, 1′′-terphenyl]-4, 4′′-dicarboxylic acid, DMF = N, N -dimethylformamide), with pcu topology was successfully synthesized and structurally characterized.JLU-MOF50 exhibits excellent chemical stability in both acidic and alkaline aqueous solutions. Due to the missing linker sites, high porosity (BET surface area of 1101 m 2 g −1 ), and excellent luminescence property, JLU-MOF50 possesses dual functionalities, which exhibits not only a commendable trapping capacity (92 mg g −1 ) and an adsorption rate (32.5 mg g −1 min −1 ), but also high detection sensitivity and selectivity for Cr2 O7 2− in an aqueous phase. It is worth mentioning that the K SV value ofJLU-MOF50 towards Cr2 O7 2− can reach up to 4.99 × 10 4 M −1, which is one of the highest values reported to date for MOF materials. Based on the aforementioned properties, JLU-MOF50 is a good candidate for fast capture and highly luminescence detection of Cr2 O7 2− simultaneously in an aqueous phase.